2020
DOI: 10.1080/02656736.2020.1782999
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of MR-guided pancreas ablation using high-intensity focused ultrasound in a healthy swine model

Abstract: Purpose: Pancreatic cancer is typically diagnosed in a late stage with limited therapeutic options. For those patients, ultrasound-guided high-intensity focused ultrasound (US-HIFU) can improve local control and alleviate pain. However, MRI-guided HIFU (MR-HIFU) has not yet been studied extensively in this context. To facilitate related research and accelerate clinical translation, we report a workflow for the in vivo HIFU ablation of the porcine pancreas under MRI guidance. Materials and methods: The pancreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Cell membrane could be damaged due to the crystal formation during the freezing cycle. In addition, rapid onset of autolysis or autodigestion and faster degradation process due to secretion of enzymes and other biofluids might affect the frozen tissue to a higher degree than the fresh tissue 43,44 . From Figure 1, the lobular structure of the tissue is clearly evident in fresh samples, but was rarely visible in the frozen samples.…”
Section: Resultsmentioning
confidence: 99%
“…Cell membrane could be damaged due to the crystal formation during the freezing cycle. In addition, rapid onset of autolysis or autodigestion and faster degradation process due to secretion of enzymes and other biofluids might affect the frozen tissue to a higher degree than the fresh tissue 43,44 . From Figure 1, the lobular structure of the tissue is clearly evident in fresh samples, but was rarely visible in the frozen samples.…”
Section: Resultsmentioning
confidence: 99%
“…In the development process for a WBTT treatment device, the 93/42/EEC medical device directive prescribes safety tests as a first mandatory step in the development of a medical device. 39 Herein, we introduced and validated an experimental setup and procedure which enables long-term WBTT in large animals and human beings; including a full anesthesia protocol also to be implemented in future clinical applications in patients. The vital organs, body fluids, vital signs and the well-being of the animal during and after treatment were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, minipigs are able to tolerate the proposed thermal dose, and previous studies already demonstrated the safety of TT applied to minipigs [36][37][38]. Interesting, Sebeke and collaborators very recently established a workflow for the in vivo high-intensity focused ultrasound ablation of the porcine pancreas under MRI guidance to facilitate related research and accelerate clinical translation [39].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of pancreatic tumors using the extracorporeal HIFU approach has also been suggested [ 16 , 36 , 49 , 50 , 51 ]. However, the surrounding digestive tract organs may be easily harmed by HIFU making the targeting difficult.…”
Section: Discussionmentioning
confidence: 99%
“…However, the diameter of this hepatic artery (5 mm) is similar to the diameter of the mesenteric artery in humans. Despite these differences, the similarities in terms of the anatomical dimensions and structure between the human and porcine pancreas make the pig the predominant model for preclinical studies on the treatment of pancreatic carcinoma with HIFU [ 24 , 31 , 32 , 33 , 34 , 35 , 36 ]. Therefore, in this study, the feasibility of selective ablation of the porcine pancreas and tissues around the peripancreatic hepatic artery using an intraoperative toroidal HIFU transducer was investigated under Doppler guidance in 20 healthy, female landrace pigs 12 to 14 weeks old and weighing between 25 and 30 kg.…”
Section: Methodsmentioning
confidence: 99%